2023
DOI: 10.17219/dmp/146635
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the wound-healing potential of the kiwifruit extract by assessing its effects on human gingival fibroblasts and angiogenesis

Abstract: We would like to thank Prof. Kishor G. Bhat and Dr. Chetana Bogar from the Department of Microbiology of the Maratha Mandal Dental College, Belgavi, India, for culturing the human gingival fibroblasts, and for providing technical assistance to carry out the MTT and scratch assays. We would also express our gratitude to Dr. Menega from Bioneemtech, Chennai, India, for helping us in conducting the CAM assay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Kiwifruit has been known to have protein-dissolving enzymes, called actinidin, ascorbic acid, pro-angiogenic and antibacterial agents. These ingredients are essential in ulcer healing processes (Hafezi et al, 2010;Mohajeri et al, 2010Mohajeri et al, , 2015 and may enhance wound healing by increasing angiogenesis and fibroblast migration (Rahman et al, 2023). Following the success in showing effectiveness of kiwifruit in treating second-degree burns in rats (Mohajeri et al, 2010), a randomized clinical trial of kiwifruit extract healed foot ulceration and chronic bedsores faster than the standard treatment, and the collagen and granulation tissue were significantly higher in the treated groups (Mohajeri et al, 2010(Mohajeri et al, , 2015.…”
Section: Includedmentioning
confidence: 99%
“…Kiwifruit has been known to have protein-dissolving enzymes, called actinidin, ascorbic acid, pro-angiogenic and antibacterial agents. These ingredients are essential in ulcer healing processes (Hafezi et al, 2010;Mohajeri et al, 2010Mohajeri et al, , 2015 and may enhance wound healing by increasing angiogenesis and fibroblast migration (Rahman et al, 2023). Following the success in showing effectiveness of kiwifruit in treating second-degree burns in rats (Mohajeri et al, 2010), a randomized clinical trial of kiwifruit extract healed foot ulceration and chronic bedsores faster than the standard treatment, and the collagen and granulation tissue were significantly higher in the treated groups (Mohajeri et al, 2010(Mohajeri et al, , 2015.…”
Section: Includedmentioning
confidence: 99%
“…Considering the facts presented so far, including the important role of GMSCs in physiological and pathological conditions, the question arises regarding how pomegranate peel extract (PoPEx) affects GMSCs because such data are missing in the literature. In this context, a paper showed that kiwifruit extract enhanced the proliferation and migration of human gingival fibroblasts and promoted angiogenesis [34]. In addition, a pomegranate extract and punicallagin exerted antioxidant properties on human gingival fibroblasts but inhibited their proliferation at higher concentrations [35].…”
Section: Introductionmentioning
confidence: 99%